An Empirical Study: Linkage between Stock Market Prices and Selected Macroeconomic Variables in Indian Context (Trinity Journal of Management, IT & Media (TJMITM), 2020)
The purpose of this study is to investigate the long run impact of selected five macroeconomic variables – CPI - Inflation rate, Gold Prices, Silver Prices, Index of Industrial Production (IIP) and Wholesale Price Index – WPI on the performance of the stock market index namely CNX by using unit tests, regression, correlation and causality of the monthly data for the period of five years from 1 April 2014 to 31 March 2019.Various statistical techniques are used in the study to analyze the input data like the ADF unit root test, Multivariate Regression analysis, Phillips-Perron (PP) Test, Correlation Analysis and Granger Causality test. All the independent variables used in the study were stationary at first level difference. The regression analysis showed that all the macroeconomic variables were found to have no significant impact on the dependent variable, i.e., CNX Nifty. Correlation test provided some useful results like, inter-variable relationship between different independent variables used. Nifty Index was found to have a positive relation with Gold, IIP and WPI and also it had a negative relation with CPI and Silver. Grange Causality test was performed on the input data and it was found that there was a causality found from Nifty to IIP.
Keywords: nnovative work behavior (IWB); ront line employees (FLE); Innovative behavior (IB) and Personal; contextual and psychological (PCP)